ChemInform Abstract: Lewis Acid‐Promoted Ketene—Alkene [2 + 2] Cycloadditions. Issue 29 (1st July 2013) - Rasik, Christopher M.; Brown, M. Kevin
Abstract Ketenes, generated in situ or isolated, react with various cyclic and linear alkenes in the presence of EtAlCl2 to afford the cycloaddition products with moderate to high diastereoselectivity.